Manajemen Event dalam Peluncuran Smartphone Flagship Terbaru dari Brand Global - Janebethia Alice Riamelia; Centurion Chandratama Priyatna (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Background: Public Relations (PR) plays a strategic role in event management, particularly as a corporate communication tool to shape a positive image and enhance media exposure. Objective: This study aims to examine how event management strategies are implemented in the launch of a flagship smartphone product by a global brand, carried out by a Public Relations consultancy. Method: A descriptive qualitative approach was employed, using data collection techniques such as direct observation, unstructured interviews, and literature review. The study focuses on the application of Goldblatt’s (2002) five-stage event management model, which includes research, design, planning, coordination, and evaluation. The findings indicate that each stage was executed systematically and in an integrated manner to build a strong and immersive brand experience. Research was conducted to identify audience needs and develop a targeted media strategy; the event design was based on a futuristic concept reflecting technological and aesthetic values; technical planning involved structured management of timing, venue, and event flow; coordination required cross-team and stakeholder collaboration; while evaluation was used to assess communication effectiveness and participant satisfaction. Results: This study highlights the critical role of Public Relations in aligning communication strategy with audience experience, and showcases best practices in collaboration between the brand, Public Relations consultants, and event organizers. The findings are expected to contribute both practically and conceptually to the development of event management strategies grounded in strategic communication within the increasingly competitive technology industry.